Pengaruh Promosi, Lokasi, Dan Kualitas Pelayanan Keputusan Pembelian Pada PT Asean Motor International Luwuk : The Influence Of Promotion, Location, And Service Quality On Purchasing Decisions At PT Asean International Luwuk - Kurubit, Arpan; Tingkepemo, Marsela; Handayani, Elisabet (Jurnal Ilmiah Produktif, 2024)
The purpose of this research is to determine the influence of promotion, location and service quality on purchasing decisions at PT Asean Motor International Luwuk. The analytical method used in this research is multiple linear regression analysis using 90 samples. Based on data processing with the help of the SPSS version 20 program, it was found that the variables promotion (X1), location (X2) and service quality (X3) had a significant influence on purchasing decisions, while the independent variables promotion, location and service quality had a strong relationship. The results of the F test prove that the variables promotion, location and service quality have a significant effect on purchasing decisions at PT Asean Motor International Luwuk Branch with Fcount 38.247 and Ftable 3.10.